Continuity equation and Gorlin formula compared with directly observed orifice area in native and prosthetic aortic valves. Issue 2 (February 1992) - Chambers, J B; Sprigings, D C; Cochrane, T; Allen, J; Morris, R; Black, M M; Jackson, G
Abstract : Orifice areas calculated by the continuity and Gorlin equations have been shown to correlate well in vivo. The continuity equation, however, gives underestimates compared with the Gorlin formula and it is not clear which is the more accurate. Both equations have therefore been tested against maximal orifice area measured by planimetry in eight prepared native aortic valves and four bioprostheses. A computer controlled, ventricular flow simulator (cycled at 70 beats/min) was used at five different stroke volumes that gave cardiac outputs of 2.8 to 7.0 l/min. The mean difference between measured and estimated orifice area was zero for the continuity equation, but -0.14 cm2 for the conventional Gorlin formula. Thus the Gorlin formula tended to give overestimates compared with both measured area and area estimated by the continuity equation, probably because of the effect of pressure recovery. When predictive equations derived from these data were tested, residual standard deviations were around 0.3 cm2 at all stroke volumes for the continuity equation, around 0.2 cm2 for the invasive Gorlin formula, and between 0.2 and 0.4 cm2 for the modified Gorlin formula. These results suggest that estimates of orifice area in an individual valve as judged by any of the equations tested should be seen as a guide to rather than as a precise measure of actual orific area.